Protease-activated receptor 1 in the pathogenesis of cystic fibrosis - Sarath Ranganathan; Philip Sutton; Sophie Day; Poshmaal Dhar; Kristy Azzopardi; Muhammad A Saeed; Sohinee Sarkar; Jia-Xi Han (BMJ Open Respiratory Research)
Background The most common cause of death in those with cystic fibrosis (CF) is respiratory failure due to bronchiectasis resulting from repeated cycles of respiratory infection and inflammation. Protease-activated receptor 1 (PAR1) is a cell surface receptor activated by serine proteases including neutrophil elastase, which is recognised as a potent modulator of inflammation. While PAR1 is known to play an important role in regulating inflammation, nothing is known about any potential role of this receptor in CF pathogenesis.Methods PAR1 (PAR1-/-) and intestinal-corrected CFTR (Cftr-/-) deficient mice were crossed to generate double knock-out (DKO) mutants lacking both PAR1 and CFTR, as well as matching sibling single mutant and wildtype (WT) littermate controls. Mice were weighed weekly to 15 weeks of age; then, the lungs and intestines were examined.Results Cftr-deficient mice gained body weight at a significantly slower rate than WT controls and presented with no lung inflammation, but had increased weights of their ilea and proximal colons. DKO mice (lacking both CFTR and PAR1) gained body weight at a similar rate to Cftr-/- mice but only gained weight in their proximal colons. Weight gain in the ilea of Cftr-/- but not DKO mice was associated with increased ileal levels in the pro-inflammatory cytokine interleukin (IL)-6.Conclusions This study provides the first evidence of PAR1 contributing to the pathological effects of Cftr deficiency in the intestine and suggests a possible effect of PAR1 on the regulation of IL-6 in CF pathogenesis.